The Effectiveness Of Typography In Packaging Design For Smes Food Industries - Md Saad, Khatijah; Idris, Muhammad Zaffwan (2014)
The purpose of this paper is to provide a review on the effectiveness of typography in packaging design for SMEs food industries. This paper presents an exposition of content analysis and visual audits methods conducted on 27 products of SMEs. Samples were taken from SMEs who participated in Karnival Usahawan Desa (KUD) 2014 in Johor Bahru. This research examined the use of typographical aspects in conveying information about the product such as type, style and shape on the packaging, as well as communication aspects such as legibility, consistency and hierarchy. Findings suggested that typography used in SMEs packaging design need to limit the number of typefaces. Too many typefaces can produce a distorted message defeating the purpose of communicating about the product. The typeface should provide a clear, consistent and unified message. It is hoped that the findings, as presented in this paper, will highlight the important of using typography effectively in order to increase consumer comprehension of the product to a much greater degree, thus increasing consumer loyalty and product sales